Perceptions of Pediatric Nephrologists regarding Timing of Dialysis Initiation in Children in Canada. Issue 1 (1st July 2016) - Saban, Jeremy A.; Zappitelli, Michael; Samuel, Susan M.; Sood, Manish M.; Alexander, R. Todd; Arora, Steven; Erickson, Robin L.; Kroeker, Kristine; Manns, Braden J.; Dart, Allison B.
Background: Significant practice variation exists in Canada with respect to timing of dialysis initiation in children. In the absence of evidence to guide practice, physicians' perceptions may significantly influence decision-making. Objective: The objectives of this study are to (1) evaluate Canadian pediatric nephrologists' perceptions regarding dialysis initiation in children with chronic kidney disease (CKD) and (2) determine the factors guiding practice that may contribute to practice variation across Canada. Design: This study was a cross-sectional online survey. Setting: This study was done in academic pediatric nephrology centers in Canada. Participants: The participants of this study are pediatric nephrologists. Measurements and methods: An anonymous web-based survey was administered to pediatric nephrologists in Canada to evaluate perspectives and practice patterns regarding timing of dialysis initiation. We also explored the importance of estimated glomerular filtration rate (eGFR) vs. symptoms and the role of patient and provider factors influencing decisions. Results: Thirty-five nephrologists (59 %) completed the survey. Most respondents care for advanced CKD patients in a multidisciplinary clinic (86 %) and no centers have a formal policy on timing of dialysis initiation. Seventy-five percent of centers follow <20 stage 4–5 CKD patients, and 9 % follow >30 patients. Discussions about dialysis initiation are generally informal (75 %) and the decision to start is made by the nephrologist (37 %) or a team (57 %). Fifty percent agreed GFR was important when deciding when to initiate dialysis, 41 % were neutral, and 9 % disagreed. Variability exists in the threshold that nephrologists considered early (vs. late) dialysis initiation: >20 (21 %), >15 (38 %), >12 (26 %), and >10 ml/min/1.73 m 2 (12 %). Practitioners however typically start dialysis in asymptomatic patients at eGFRs of 7–9 (9 %), 10–11 (41 %), 12–14 (38 %), and 15–19 (6 %) ml/min/1.73 m 2 . Patient factors important in the decision to start dialysis for >90 % of nephrologists were fatigue, >10 % weight loss, nausea, increasing missed school, and awaiting a pre-emptive transplant. Age was only a factor for 56 %. Limitations: This study has a 59 % response rate. Conclusions: Variability exists in Canada regarding the importance and threshold of eGFR guiding the decision as to when to start dialysis in children, whereas patient symptoms are almost universally important to pediatric nephrologists' decision-making. Additional studies evaluating outcomes of children starting dialysis earlier vs. later are needed to standardize decision-making and care for children with kidney failure.